Additional cash Incentive within a conditional cash transfer scheme: A 'controlled before and during' design evaluation study from India - Chandrakant Lahariya; Ashok Mishra; Deoki Nandan; Praveen Gautam; Sanjay Gupta (Wolters Kluwer Medknow Publications, 2011)
Background : Conditional Cash Transfer (CCT) schemes have shown largely favorable changes in the health seeking behavior. This evaluation study assesses the process and performance of an Additional Cash Incentive (ACI) scheme within an ongoing CCT scheme in India, and document lessons. Material and Methods: A controlled before and during design study was conducted in Madhya Pradesh state of India, from August 2007 to March 2008, with increased in institutional deliveries as a primary outcome. In depth interviews, focus group discussions and household surveys were done for data collection. Results: Lack of awareness about ACI scheme amongst general population and beneficiaries, cumbersome cash disbursement procedure, intricate eligibility criteria, extensive paper work, and insufficient focus on community involvement were the major implementation challenges. There were anecdotal reports of political interference and possible scope for corruption. At the end of implementation period, overall rate of institutional deliveries had increased in both target and control populations; however, the differences were not statistically significant. No cause and effect association could be proven by this study. Conclusions: Poor planning and coordination, and lack of public awareness about the scheme resulted in low utilization. Thus, proper IEC and training, detailed implementation plan, orientation training for implementer, sufficient budgetary allocation, and community participation should be an integral part for successful implementation of any such scheme. The lesson learned this evaluation study may be useful in any developing country setting and may be utilized for planning and implementation of any ACI scheme in future.